O benefício eventual da LOAS como garantia de proteção social - Bovolenta, Gisele Aparecida (2016)
This study investigates the scenery and the history of progress and challenges, continuities and changes in the recognition of the Brazilian government potential benefits (BE). BE are under the responsibility of the social welfare policy since 1993 and are a social assistance right in the sector of distributive social protection. BE have established a public state duty to support citizens in view of life cycle events, such as birth and death, and day-to-day hardships, such as temporary vulnerability, lack of social protection and public calamity. The cities, states and the Federal District are responsible for ensuring such right, thus it is necessary to consider the cooperation agreement regarding management, regulation and funding signed by these organizations before the Federative Agreement. Based on real-life data and through evidence-based, theoretical, documentary and legal analyses, this research sought to rebuild the history of such benefits, identify previous forms of care, investigate their elements and make a few considerations about the current BE provided. Finally, this study aims to perform an evidence-based reality analysis of the city and the state of São Paulo, highlighting the lack of cooperation among the organizations responsible for ensuring such social assistance right, which is part of the social protection sector of the Brazilian Unified Social Assistance System (SUAS)